Neural responses to sounds presented on and off the beat of ecologically valid music - Tierney, Adam; Kraus, Nina (Frontiers in Systems Neuroscience, 2013)
The tracking of rhythmic structure is a vital component of speech and music perception. It is known that sequences of identical sounds can give rise to the percept of alternating strong and weak sounds, and that this percept is linked to enhanced cortical and oscillatory responses. The neural correlates of the perception of rhythm elicited by ecologically valid, complex stimuli, however, remain unexplored. Here we report the effects of a stimulus’ alignment with the beat on the brain’s processing of sound. Human subjects listened to short popular music pieces while simultaneously hearing a target sound. Cortical and brainstem electrophysiological onset responses to the sound were enhanced when it was presented on the beat of the music, as opposed to shifted away from it. Moreover, the size of the effect of alignment with the beat on the cortical response correlated strongly with the ability to tap to a beat, suggesting that the ability to synchronize to the beat of simple isochronous stimuli and the ability to track the beat of complex, ecologically valid stimuli may rely on overlapping neural resources. These results suggest that the perception of musical rhythm may have robust effects on processing throughout the auditory system.